Efeitos de raios gama sobre trypanosoma cruzi. II. Anticorpos em camundongos inoculados com formas de cultura - Salata, E.; Barbosa, M. A.; Correa, F. M. A. (My University, 1976)
Antibody fluorescent tests were carried out with serum and blood eluates from mice inoculated with different doses of irradiated (90 krad) and non irradiated T. cruzi culture forms. Non irradiated culture forms were more efficient immunogens than the irradiated ones. About 75% of the animals inoculated with non irradiated forms showed titers equal or higher than 1/16, the highest one reaching 1/64.
Effects of gamma radiation on Trypanosoma cruzi. II. Antibody production in mice inoculated with culture forms
Keywords: trypanosoma cruzi; Animal; Antibody Formation; English Abstract; Gamma Rays; Immunization; Mice; Trypanosoma cruzi